Genome-wide profiling of genetic synthetic lethality identifies CDK12 as a novel determinant of PARP1/2 inhibitor sensitivity - Bajrami, Ilirjana (Cancer Res, 2013)
Small molecule inhibitors of PARP1/2 such as olaparib have been proposed to serve as a synthetic lethal therapy for cancers that harbor BRCA1 or BRCA2 mutations. Indeed, in clinical trials PARP1/2 inhibitors elicit sustained anti-tumor responses in patients with germ-line BRCA gene mutations. In hypothesizing that additional genetic determinants might direct use of these drugs, we conducted a genome-wide synthetic lethal screen for candidate olaparib sensitivity genes. In support of this hypothesis, the set of identified genes included known determinants of olaparib sensitivity, such as BRCA1, RAD51 and Fanconi’s anemia susceptibility genes. Additionally, the set included genes implicated in established networks of DNA repair, DNA cohesion and chromatin remodelling, none of which were known previously to confer sensitivity to PARP1/2 inhibition. Notably, integration of the list of candidate sensitivity genes with data from tumor DNA sequencing studies identified CDK12 deficiency as a clinically relevant biomarker of PARP1/2 inhibitor sensitivity. In models of high-grade serous ovarian cancer (HGS-OVCa), CDK12 attenuation was sufficient to confer sensitivity to PARP1/2 inhibition, suppression of DNA repair via homologous recombination and reduced expression of BRCA1. As one of only nine genes known to be mutated in HGS-OVCa, CDK12 has properties that should confirm interest in its utility as a biomarker, particularly in ongoing clinical trials of PARP1/2 inhibitors and other agents that trigger replication fork arrest.